Mechanism of Palladium-Catalyzed Diene Cyclization/Hydrosilylation: Direct Observation of Intramolecular Carbometalation - Perch, Nicholas S; Widenhoefer, Ross A (Journal of the American Chemical Society, 2004)
The results of kinetic, deuterium-labeling, and low-temperature NMR studies have established a mechanism for the palladium-catalyzed cyclization/hydrosilylation of dimethyl diallylmalonate (1) with triethylsilane involving rapid, irreversible conversion of the palladium silyl complex [(phen)Pd(SiEt3)(NCAr)]+ [BAr4]- [Ar = 3,5-C6H3(CF3)2] (4b) and 1 to the palladium 5-hexenyl chelate complex {(phen)Pd[η1,η2-CH(CH2SiEt3)CH2C(CO2Me)2CH2CHCH2]}+ [BAr4]- (5), followed by intramolecular carbometalation of 5 to form the palladium cyclopentylmethyl complex [BAr4]- (6), and associative silylation of 6 to release 3 and regenerate 4b.